Given the Quadratic Equation:
![2x^2-9x+8=0](https://img.qammunity.org/2023/formulas/mathematics/college/1aqv7k98xzx1js1imn89pmfkzxmgikxkg1.png)
You need to use the Quadratic Formula in order to solve it:
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
Notice that the equation is written in this form:
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
Then, in this case:
![\begin{gathered} a=2 \\ b=-9 \\ c=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2twla6n80i46lqek4rxt3wggmp8g17cql1.png)
Now you can substitute values into the formula and evaluate:
![\begin{gathered} x=(-(-9)\pm√((-9)^2-4(2)(8)))/((2)(2)) \\ \\ x=(9\pm√(17))/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a83ex56dhgltyqfq69r1loid621lze1s8r.png)
Notice that you get two values:
![x_1=(9+√(17))/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/5s428dd25p02qykw6k5ev27rjnjwc3qn45.png)
![x_2=(9-√(17))/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/ews8jtzln6j9jk8ig0b24lpg9a911fx5tk.png)
Hence, the answer is:
![x=(9+√(17))/(4)\text{ or }x=(9-√(17))/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/d0b9z6r24lg1evptrc03gojxzz8oyg4onm.png)